2005
DOI: 10.1098/rspa.2005.1494
|View full text |Cite
|
Sign up to set email alerts
|

The power potential of tidal currents in channels

Abstract: Interest in sources of renewable energy has led to increasing attention being paid to the potential of strong tidal currents. There is a limit to the available power, however, as too many turbines will merely block the flow, reducing the power generated. The maximum average power available from a tidal stream along a channel, such as that between an island and the mainland, is estimated and found to be typically considerably less than the average kinetic energy flux in the undisturbed state through the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
312
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(335 citation statements)
references
References 6 publications
20
312
3
Order By: Relevance
“…Foreman et al (2004) included the Discovery Islands region in their data assimilating, barotropic, finite element model of the waters around Vancouver Island, but in this case the primary focus was M 2 tidal dissipation. Sutherland et al (2007) used a similar two-dimensional (2-D) model to estimate the tidal power potential obtained by inserting turbine farms in Johnstone Strait, Discovery Passage and Cordero Channel and found them to be very close to the analytical estimates provided by Garrett and Cummins (2005). This was a refinement of similar studies carried out for BC Hydro (2002) for all British Columbia waters.…”
Section: Introductionmentioning
confidence: 70%
“…Foreman et al (2004) included the Discovery Islands region in their data assimilating, barotropic, finite element model of the waters around Vancouver Island, but in this case the primary focus was M 2 tidal dissipation. Sutherland et al (2007) used a similar two-dimensional (2-D) model to estimate the tidal power potential obtained by inserting turbine farms in Johnstone Strait, Discovery Passage and Cordero Channel and found them to be very close to the analytical estimates provided by Garrett and Cummins (2005). This was a refinement of similar studies carried out for BC Hydro (2002) for all British Columbia waters.…”
Section: Introductionmentioning
confidence: 70%
“…the addition of a second and third row of turbines at a given location does not double and triple the available power. This well-known result is due to the fact that although adding rows to an array does increase its total power output, it also increases the resistance to flow through the array, thereby reducing the amount of power available to the turbines within it (Garrett and Cummins 2005;Vennell 2010). The sub-grid-scale actuator disc model also enables comparison, in terms of power per swept area, between different development options.…”
Section: Resource Assessmentmentioning
confidence: 99%
“…1). Harmonic analysis of these datasets reveals five significant tidal constituents, but, to simplify calibration, only the largest of these, which are expected to contribute disproportionately to the available power (Garrett and Cummins 2005;Adcock et al 2014), are used. The eastern and western flow boundaries are forced with M2 and S2 tides, the amplitudes of which are adjusted to improve the agreement between the water level results and the TotalTide predictions.…”
Section: Model Detailsmentioning
confidence: 99%
“…As the calculation in KMLH [4] illustrates, calculating this flow is essential in determining the power potential of a channel and the impact that power extraction will have on the flow through the channel. Recently, Vennell [13] illustrated that the turbine fence model of Garrett & Cummins [9] could be combined with the power theory of Garrett & Cummins [5] to determine the power potential of a partial turbine fence in a given tidal flow. His analysis illustrated a couple of key points.…”
Section: Theoretical Assessment Of Turbine Fencesmentioning
confidence: 99%
“…A more recent assessment of the power potential of Minas Passage was presented by Karsten, McMillan, Lickley and Haynes [4] (hereafter KMLH). KMLH adapted the results of Garrett & Cummins [5] to the case of a channel connecting a tidal basin to the ocean. They found that the maximum extractable mean power is given by…”
Section: Introductionmentioning
confidence: 99%